ANALISIS KOROSI DAN KERAK PIPA NICKEL ALLOY N06025 PADA WASTE HEAT BOILER - Ardhi Sudradjat; Athanasius Priharyoto Bayuseno (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2013)
Corrosion is destruction process of metal surfaces by chemical reaction from its environment. One of example is corosive media for ferrule pipe due to high temprature. The rate of corrosion is accelerated by the existance of leaks in the water feed tube. Corrosion testing on corroded ferrule pipe specimens is using SEM, EDX, and XRD examination. High temperature corrosion exist due to chloride penetration of boiler tube leak. In addition, the temperature during the test is also one factor of corrosion. Plumbing materials is damaged by high temperature corrosion. Ferrule pipe seems to increase the thickness of pipe due to the crust and thin oxidation layer. The reason of high temperature corrosion due to an oxide layer. The oxide layer able to resist attack of another corrosion if amount of oxygen in their environment is sufficient.By using the reference, there is a white crust and increased thickness of the pipe. The pipe ferrule having obtained corrosion, crust generated from the boiler tube. SEM of the test results shows that the addition of the pipe thickness due to crustal and XRD test results are minerals that cause the crust.